Letters, fictions, lives : Henry James and William Dean Howells - James, Henry, 1843-1916.; Howells, William Dean, 1837-1920.; Anesko, Michael (New York : Oxford University Press, 1997)
This volume attempts to determine the early influence shared between William Dean Howells and Henry James by reconstructing and evaluating documentary evidence of their literary cross-fertilization. The 151 letters included represent each writer's most significant criticism of the other.
Abbreviations; A Note on Editorial Procedure; PART ONE: ARRIVALS AND DEPARTURES; Biographical Overview; Parallel Chronology; A Season in Cambridge; Complex Fates; The Larger Success; Notes; Letters and Documents; PART TWO: FEARFUL RESPONSIBILITIES; Biographical Overview; Parallel Chronology; "Those Badly Assorted Siamese Twins"; The Art of Fiction; Complicity; Notes; Letters and Documents; PART THREE: LEGENDS OF MASTERY; Biographical Overview; Parallel Chronology; The Great Goethe, the Good Schiller; Testamentary Acts; Terminations; Notes; Letters and Documents; Epilogue.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: James, Henry, -- 1843-1916 -- Correspondence; Howells, William Dean, -- 1837-1920 -- Correspondence; Howells, William Dean, -- 1837-1920; James, Henry, -- 1843-1916; Authors, American -- 19th century -- Correspondence; Authors, American -- 20th century -- Correspondence; Novelists, American -- 19th century -- Correspondence; Novelists, American -- 20th century -- Correspondence; Critics -- United States -- Correspondence; Fiction -- Authorship; Écrivains américains -- 19e siècle -- Correspondance; Écrivains américains -- 20e siècle -- Correspondance; Romanciers américains -- 19e siècle -- Correspondance; Romanciers américains -- 20e siècle -- Correspondance; Critiques -- États-Unis -- Correspondance; Roman -- Art d'écrire.; BIOGRAPHY & AUTOBIOGRAPHY -- Literary; LITERARY CRITICISM -- American -- General; Authors, American; Critics; Fiction -- Authorship; Novelists, American; United States; 1800-1999; Electronic book; Biography; personal correspondence; Biographies; Personal correspondence; Biographies; Personal correspondence; Biographies; Correspondance privée.